1987
DOI: 10.1148/radiology.162.2.3797651
|View full text |Cite
|
Sign up to set email alerts
|

Lung lesions: cytologic diagnosis by fine-needle biopsy.

Abstract: Small-bore (22- or 23-gauge) needles were used to aspirate 458 lung masses. Sensitivity for the detection of malignancy by this method was 96.6% (312 of 323 patients); accuracy was 98.7%. Surgical confirmation was available for comparison in over half of patients with malignancy. Histologic reclassification of malignancy occurred in only 6.1% of patients, with significant misclassification (misdiagnosis of small cell carcinoma) occurring in only two instances. One hundred thirteen of 117 nonmalignant condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
57
1
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(71 citation statements)
references
References 0 publications
10
57
1
3
Order By: Relevance
“…The sensitivity of FNAC for diagnosing malignancy was found to be 92.59% in our study. This finding is similar to the study done by Singh et al, Stanley et al and Basnet et al 7,13,14 CT guided biopsy was positive in all patients. Small cell carcinoma was seen in 5 (6.17%) patients while nonsmall cell lung carcinoma was seen in 75 (92.59%) patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The sensitivity of FNAC for diagnosing malignancy was found to be 92.59% in our study. This finding is similar to the study done by Singh et al, Stanley et al and Basnet et al 7,13,14 CT guided biopsy was positive in all patients. Small cell carcinoma was seen in 5 (6.17%) patients while nonsmall cell lung carcinoma was seen in 75 (92.59%) patients.…”
Section: Discussionsupporting
confidence: 92%
“…Mean age of presentation was 60.98 yrs which is similar to a study done by Noronha et al 11 We found Non-small cell lung carcinoma, proven on CT guided biopsy, in 75 patients (92.59%) and small cell carcinoma in 6 patients. These findings are similar to the studies done by Shetty et al and Singh et al 12,13 CT guided FNAC yielded positive result in 75 patients. Out of these 75 patients, specific type of lung cancer was confirmed in 58 patients.…”
Section: Discussionsupporting
confidence: 92%
“…omputed tomography (CT)-guided transthoracic fine needle aspiration (TTFNA) biopsy is currently considered a reliable diagnostic technique to assess malignancy of pulmonary nodules and masses (1)(2)(3)(4). CT-guided TTFNA is an invasive technique with low incidence of severe complications and contraindications (1).…”
mentioning
confidence: 99%
“…Pneumothorax is the most common complication occurring in the range of 8%-64% (with a risk of tension pneumothorax in about 7% of cases) (1)(2)(3)(4)(5)(6)(7). The risk of pneumothorax increases in the presence of obstructive lung disease and small target lesion.…”
mentioning
confidence: 99%
“…This ensures proper needle placement and helps to avoid the necrotic areas. Carefully performed transthoracic needle or Tru-cut biopsy can result in an extremely high accuracy rate (90% -98%) of diagnosis of cancer [7][8][9], They are often helpful in indicating the histologic typing of the lesions (77%-83%) [3]. In our series, the diagnosis of malignancy and cell typing were possible in almost all cases.…”
Section: Discussionmentioning
confidence: 71%